CASE STUDY: A GREAT RECOVERY OF MALAYSIA AIRLINESCASE STUDY: A GREAT RECOVERY OF MALAYSIA AIRLINES - Yajid, Mohd Shukri Ab; Indang; Khatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The aim about this study is to explore the causes of airline recovery in Malaysia. Airline industry is one of the most competitive and strongest industries in the world. The speed of air traveling and the fall of real prices have made the air traveling increased in market share of passenger transport. Furthermore, the fatalities and the long term safety record of air traveling are way better than any other modes of transportation. One of the most controversial airlines in Asia, Malaysian Airline System (MAS), has been praised and criticized in equal measures. Malaysia Airlines’ humble origins began in the golden age of travel in 1937. By the end of 1947, once known as Malayan Airways had engaged in an expansion exercise to cater to the growing needs of a growing nation. Within three months, the company broke the borders of domestic service to offer flights to neighborhood countries. A year after the Independence of Malaya in 1957, Malayan Airways took the next step in becoming part of the new corporate scene in Malaysia and was launched as a public limited company. The advancement continues to the acquisition of an 82- seater Briston Britania in 1960 made mass transport by air a reality. This led to the first international non-stop service for MAL, which operated directly between Kuala Lumpur and Hong Kong (Wong & Musa, 2011; De Silva et al., 2018a; De Silva et al., 2018b; Nikhashemi et al., 2013).